MENDALAMI DOKTRIN TRINITAS DALAM PANDANGAN HANS URS VON BALTHASAR - Markus Situmorang (Litbang STFT Widya Sasana Malang, 2018)
All the Hans Urs von Balthasar theology is the Trinity. For him everything flows from interpersonal relationships in the Trinity. The starting point for understanding the Trinity must depart from the event of love. Jesus is a manifestation of God’s love that appears to humans. God’s love is beautiful. Jesus revealed the beauty of the Triune God. The fundamental aspect of beauty is obedience from Jesus. Jesus as the beauty that manifest the Father and the Holy Spirit. We will not be able to understand the beauty of Christ without referring to inter-Trinitarian beauty. It does not stop at mere beauty but God is involved in the history of human life. In other words, God is involved in drama with humans. On the Good Friday, there was a drama between God and the world on the cross. But a more dramatic drama took place on Holy Saturday. Drama also occurs in the life of the Trinity. The three divine persons empty themselves which are united in a bond of love. The real kenosis occurs in a triune life. The Trinity lives in the Church and maintains the Church. The church’s teachings are undeniable because of the truth of the Trinity itself. Seluruh teologi Hans Urs von Balthasar adalah Tritunggal. Baginya segala sesuatu mengalir dari relasi antar pribadi dalam Tritunggal. Titik tolak untuk memahami Tritunggal harus berangkat dari peristiwa kasih. Yesus adalah wujud kasih Allah yang tampak kepada manusia. Kasih Allah sendiri sangat indah. Yesus mewahyukan keindahan dari Allah Tritunggal. Aspek fundamental dari keindahan itu yakni ketaatan dari Yesus. Yesus sebagai keindahan yang mewahyukan Bapa dan Roh Kudus. Wujud dari Yesus mengacu kepada wujud dari Allah dalam diri-Nya sendiri.Trinitas seperti cinta di dalam dirinya sendiri. Kita tidak akan dapat memahami keindahan Kristus tanpa mengacu pada keindahan inter-Trinitaris. Tidak berhenti pada keindahan semata tetapi Allah terlibat di dalam sejarah kehidupan manusia. Dengan kata lain Allah terlibat drama dengan manusia. Pada peristiwa Jumat Agung terjadi drama antara Allah dan dunia di kayu salib. Namun drama yang lebih dramatis terjadi pada Sabtu Suci. Drama juga terjadi juga di dalam kehidupan Tritunggal. Tiga pribadi ilahi saling mengosongkan diri yang disatukan dalam ikatan cinta. Tritunggal itu yang hidup di dalam Gereja dan memelihara Gereja. Ajaran-ajaran Gereja tidak terbantahkan karena kebenaran Tritunggal itu sendiri.